1998
DOI: 10.1128/mcb.18.3.1248
|View full text |Cite
|
Sign up to set email alerts
|

Two Members of the Tcf Family Implicated in Wnt/β-Catenin Signaling during Embryogenesis in the Mouse

Abstract: Tcf transcription factors interact with ␤-catenin and Armadillo to mediate Wnt/Wingless signaling. We now report the characterization of genes encoding two murine members of the Tcf family, mTcf-3 and mTcf-4. mTcf-3 mRNA is ubiquitously present in embryonic day 6.5 (E6.5) mouse embryos but gradually disappears over the next 3 to 4 days. mTcf-4 expression occurs first at E10.5 and is restricted to di-and mesencephalon and the intestinal epithelium during embryogenesis. The mTcf-3 and mTcf-4 proteins bind a cano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
229
1
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 303 publications
(243 citation statements)
references
References 45 publications
12
229
1
1
Order By: Relevance
“…In the microarray analysis, we observed a 55% increase in P2rx4 expression with age in +/sh2 heterozygotes, but only a 24% increase in sh2/sh2 mice. Tcf3 encodes a transcription factor implicated in Wnt/b-catenin signaling in early embryogenesis (Korinek et al 1998). In this study, Tcf3 showed a small but consistent decrease (14%) with age in sh2/sh2 mice, but no age-related change in +/sh2 mice.…”
Section: Genes With Age and Genotype Effectssupporting
confidence: 48%
See 1 more Smart Citation
“…In the microarray analysis, we observed a 55% increase in P2rx4 expression with age in +/sh2 heterozygotes, but only a 24% increase in sh2/sh2 mice. Tcf3 encodes a transcription factor implicated in Wnt/b-catenin signaling in early embryogenesis (Korinek et al 1998). In this study, Tcf3 showed a small but consistent decrease (14%) with age in sh2/sh2 mice, but no age-related change in +/sh2 mice.…”
Section: Genes With Age and Genotype Effectssupporting
confidence: 48%
“…b-Catenin and TCF3/LEF DNA-binding proteins form bipartitate complexes that are translocated to the nucleus to transactivate downstream genes, such as WISP1 (Xu et al 2000). In the absence of stabilized b-catenin, TCF3 can act as a repressor and plays a critical role in axis formation in the early embryo (Korinek et al 1998;Merrill et al 2004). WISP1 plays an important role as an osteoblastic regulator, promoting ostoblast differentiation and chondrocyte proliferation during embryonic skeletal development and repair of fractured bones (French et al 2004).…”
Section: Genes With Age-related Changesmentioning
confidence: 99%
“…19 The same study also indicated that SOX6 can suppress cyclin D1 activity by interacting with b-catenin and histone deacetylase 1. 20 However, using a TOPFlash (T-cell factor reporter plasmid) assay, 21 we were unable to demonstrate that SOX6 overexpression resulted in the suppression of wnt signaling activity.…”
Section: Discussionmentioning
confidence: 87%
“…However, the role of TLE in modulating Tcf4-dependent Wnt activity is controversial. A mouse TLE homolog does not bind to mouse Tcf4 in a yeast 2-hybrid assay, 57 and mouse and human Tcf4 share 98% amino acid homology; 58 however, a more recent study has demonstrated that TLE co-repressors could inhibit the transcriptional activity of all Tcf factors. 59 Further study is necessary to delineate the role, if any, of TLE factors in the de-repression of Wnt activity in butyrate-treated HCT-116 cells.…”
Section: Discussionmentioning
confidence: 94%